(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
This experimental study was conducted at the animal farm of the College of Veterinary Medicine of Baghdad University during the period 15/3/2019 until 30/4/2019. Fourteen female local breed goats, at aged between 1.5–2 years and range weight 23–27kg.The animals were divided into two equal groups as following G1(control) was fed on concentrate diet 2% B.W and alfa - alfa hay .G2 group was fed the same diet and 2% grinding Mulberry leaves of concentrate diet .water was offered freely. For evaluation some animal performance. Bodyweight, some nutrients digestibility, blood picture and biochemical parameters. Results revealed that an excellent improvement was observed in body weight and nutrients digestibility were significantly (P<0.05). Similar effects in blood biochemical parameters (total protein and urea), while no differences were determined in triglycerides and cholesterol. other blood parameters showed that hemoglobin (Hb) and packed cell volume (PCV) which were significantly higher (P <0.05) and further improved in erythrocytes, leucocytes, lymphocytes and neutrophils in the group received Mulberry leaves than control groups.